Effect of passive smoking exposure on risk of type 2 diabetes: a systematic review and meta-analysis of prospective cohort studies - Qin, Guo-Qiang; Chen, Li; Zheng, Jun; Wu, Xiao-Min; Li, Yang; Yang, Kai; Liu, Tong-Feng; Fang, Zhong-Ze; Zhang, Qiang (Frontiers in Endocrinology, 2023)
Objective: The effect of passive smoking exposure on the risk of type 2 diabetes has not been systematically studied. A meta-analysis was conducted to assess the association between passive smoking exposure and the risk of diabetes.Methods: We searched three major databases up to 31 October 2022 to identify relevant prospective cohort studies on the association between passive smoking and the risk of type 2 diabetes. The pooled relative risk (RR) and 95% confidence interval (CI) for the association between passive smoking exposure and the risk of type 2 diabetes were analyzed using a fixed effect model. Results: 10 prospective cohort studies were included in this meta-analysis, with a total of 251,620 participants involved. The pooled RR showed a significantly positive association between nonsmokers exposed to passive smoking and type 2 diabetes as compared to non-smokers who were not exposed to passive smoking (RR = 1.27, 95% CI [1.19, 1.36]; p < 0.001). Sensitivity analysis indicated that the pooled RR was not substantially affected by any of the individual studies.Exposure to passive smoking increases the risk of type 2 diabetes. This study may have a positive effect on the prevention of type 2 diabetes.